1997
DOI: 10.1002/(sici)1097-4636(199704)35:1<107::aid-jbm11>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer foam morphology and density on kinetics of in vitro controlled release of isoniazid from compressed foam matrices

Abstract: The purpose of this study was to compare the effect of polymer foam morphology and density prior to compaction on the kinetics of isoniazid (INH) release from the final highdensity extruded matrices. The feasibility of preparing low density foams of several biopolymers, including poly(Llactide) (PLLA), poly(glycolide) (PGA), poly(DL-lactide-coglycolide) (PLGA), poly(␥-benzyl-L-glutamate) (PBLG), and poly(propylene fumarate) (PPF), via a lyophilization technique was investigated. Low-density foams of PLGA, PBLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…Pore size ranges were determined using digital image processing of SEM images. Scaffold porosity was determined using an ethanol displacement method similar to that reported by Zhang and Ma (25), Hsu et al (11), and reported by our group previously (10). Scaffold samples were individually immersed in a cylinder containing a known volume of ethanol (V 1 ).…”
Section: Scaffold Characterizationmentioning
confidence: 95%
“…Pore size ranges were determined using digital image processing of SEM images. Scaffold porosity was determined using an ethanol displacement method similar to that reported by Zhang and Ma (25), Hsu et al (11), and reported by our group previously (10). Scaffold samples were individually immersed in a cylinder containing a known volume of ethanol (V 1 ).…”
Section: Scaffold Characterizationmentioning
confidence: 95%
“…Pore sizes were calculated from SEM images by Image J software (National Institutes of Health). Scaffold porosity was determined by a liquid displacement method [26,27]. Ethanol was used as the displacement liquid.…”
Section: Scaffold Characterizationmentioning
confidence: 99%
“…These conventional scaffold fabrication techniques include solvent casting-particulate leaching [66,79], gas foaming [17], fiber meshes/fiber bonding [80,81], melt molding [82,83], and thermal phase separation/freeze drying [36,37,[84][85][86][87][88][89].…”
Section: Scaffold Fabrication Techniquesmentioning
confidence: 99%